2017
DOI: 10.1093/gbe/evx242
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics of Pathogenic and Nonpathogenic Beetle-Vectored Fungi in the Genus Geosmithia

Abstract: Geosmithia morbida is an emerging fungal pathogen which serves as a model for examining the evolutionary processes behind pathogenicity because it is one of two known pathogens within a genus of mostly saprophytic, beetle-associated, fungi. This pathogen causes thousand cankers disease in black walnut trees and is vectored into the host via the walnut twig beetle. Geosmithia morbida was first detected in western United States and currently threatens the timber industry concentrated in eastern United States. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 107 publications
2
14
0
Order By: Relevance
“…These characteristics make microscopic fungi an important food source for soil invertebrates such as Arthropoda, Annelida, Mollusca or Nematoda (Johnson et al, ; Crowther, Boddy & Jones, , ; Crowther, Boddy & Hefin, ). Some species of termites, ants or beetles (Mueller & Gerardo, ; Mueller et al, ; Schuelke et al, ), as well as certain snails (Silliman & Newell, ), are known to culture fungal biomass and use it as a primary food source. Many macroscopic fruiting bodies and lichen thalli are edible and constitute an important food source for animals, including humans (de Mattos‐Shipley et al, ).…”
Section: Fungi and Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…These characteristics make microscopic fungi an important food source for soil invertebrates such as Arthropoda, Annelida, Mollusca or Nematoda (Johnson et al, ; Crowther, Boddy & Jones, , ; Crowther, Boddy & Hefin, ). Some species of termites, ants or beetles (Mueller & Gerardo, ; Mueller et al, ; Schuelke et al, ), as well as certain snails (Silliman & Newell, ), are known to culture fungal biomass and use it as a primary food source. Many macroscopic fruiting bodies and lichen thalli are edible and constitute an important food source for animals, including humans (de Mattos‐Shipley et al, ).…”
Section: Fungi and Animalsmentioning
confidence: 99%
“…Such factors are likely to result in an increased genome size, which in turn requires a higher nutritional intake to meet DNA biosynthesis and the production of dispersion structures. Thus, as a general rule, host‐restricted necrotrophic plant pathogens tend to have smaller genomes and fewer protein‐coding genes than broad‐spectrum pathogens (Marcet‐Houben et al, ; O'Connell et al, ; Julca et al, ; Schuelke et al, ).…”
Section: The Fungus–plant Biome: Ecological Interactions Between Planmentioning
confidence: 99%
“…The length of coding sequences per gene (Table S2; pANOVA: F = 3.62, p = 0.168; pairwise p adj : free livingfacultative = 0.117, free living-specialist = 0.195, facultative-specialist = 0.646) and mean intron length (Table S2; pANOVA: F = 1.25, p = 0.472; pairwise p adj : free living-facultative = 0.994, free living-specialist = 0.639, facultative-specialist = 0.639) did not differ significantly between life histories either; suggesting overall gene loss, rather than a reduction in coding sequence length or a decrease in intron content, is one of the factors driving genome reduction. Genome reduction, and subsequent gene loss, is common during transitions to obligate symbiosis (McCutcheon and Moran, 2012) and associated with increased specialization by a pathogenic (de Man et al, 2016;Schuelke et al, 2017) or mutualistic (Kooij and Pellicer, 2020;Nagendran et al, 2009) symbiont. Our findings are consistent with this and thus suggest that these clades are most likely obligate specialist symbionts of termite hosts.…”
Section: Genome Reduction In the Transition To A Symbiotic Lifestylementioning
confidence: 99%
“…This pattern also holds true when compared to other tree pathogens. In a recent comparative genomic analysis of tree pathogens, it was reported that the black walnut pathogen, Geosmithia morbida , had 406 CAZymes, the lodgepole pine pathogen Grosmania clavigera had 530 CAZymes, and the plane tree canker pathogen, Ceratocystis platani , had 360 CAZymes [23]. Since secreted CAZymes are involved in degrading plant cell walls [22], the large number of secreted CAZymes in Oc-j might help facilitate its life-style infecting and colonizing butternut trees.…”
Section: Resultsmentioning
confidence: 99%